Active management of food allergy: an emerging concept. Issue 4 (5th November 2014) - Anagnostou, Katherine; Stiefel, Gary; Brough, Helen; du Toit, George; Lack, Gideon; Fox, Adam T
Abstract : IgE-mediated food allergies are common and currently there is no cure. Traditionally, management has relied upon patient education, food avoidance and the provision of an emergency medication plan. Despite this, food allergy can significantly impact on quality of life. Therefore, in recent years, evolving research has explored alternative management strategies. A more active approach to management is being adopted, which includes early introduction of potentially allergenic foods, anticipatory testing, active monitoring, desensitisation to food allergens and active risk management. This review will discuss these areas in turn.